Meningkatkan Kebugaran Jasmani pada Komponen Kecepatan Melalui Estafet Kerucut pada Peserta Didik Kelas VI SDN Pakis 1 - Nisa Galuh Tiara; Anung Priambodo; Marsudianto Marsudianto (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This study aims to improve students' speed skills through the implementation of the cone relay game method in Physical Education and Health (PJOK) for sixth-grade students at SDN Pakis 1. This research employs the Classroom Action Research (CAR) method, consisting of two cycles, where each cycle involves planning, action, observation, and reflection. The research subjects are 26 sixth-grade students. Data collection was carried out through speed skill tests and student activity observations. The results of the study show a significant improvement in students' speed skills following the application of the cone relay game method. In the second cycle, most students reached good and excellent categories in speed skills. Additionally, this method positively impacted students' motivation to participate in PJOK learning. Thus, the cone relay game can serve as an effective alternative method to enhance students' speed skills.